Caplacizumab Treatment for Acquired Thrombotic Thrombocytopenic Purpura. - Scully, M.; Cataland, S. R.; Peyvandi, Flora; Coppo, P.; Knobl, P.; Hovinga, J. A. Kremer; Metjian, A.; De La Rubia, J.; Pavenski, K.; Callewaert, F.; Biswas, D.; De Winter, H.; et al. (New England Journal of Medicine, 2019)
BACKGROUND: In acquired thrombotic thrombocytopenic purpura (TTP), an immune-mediated deficiency of the von Willebrand factor-cleaving protease ADAMTS13 allows unrestrained adhesion of von Willebrand factor multimers to platelets and microthrombosis, which result in thrombocytopenia, hemolytic anemia, and tissue ischemia. Caplacizumab, an anti-von Willebrand factor humanized, bivalent variable-domain-only immunoglobulin fragment, inhibits interaction between von Willebrand factor multimers and platelets. METHODS: In this double-blind, controlled trial, we randomly assigned 145 patients with TTP to receive caplacizumab (10-mg intravenous loading bolus, followed by 10 mg daily subcutaneously) or placebo during plasma exchange and for 30 days thereafter. The primary outcome was the time to normalization of the platelet count, with discontinuation of daily plasma exchange within 5 days thereafter. Key secondary outcomes included a composite of TTP-related death, recurrence of TTP, or a thromboembolic event during the trial treatment period; recurrence of TTP at any time during the trial; refractory TTP; and normalization of organ-damage markers. RESULTS: The median time to normalization of the platelet count was shorter with caplacizumab than with placebo (2.69 days [95% confidence interval CI, 1.89 to 2.83] vs. 2.88 days [95% CI, 2.68 to 3.56], P=0.01), and patients who received caplacizumab were 1.55 times as likely to have a normalization of the platelet count as those who received placebo. The percentage of patients with a composite outcome event was 74% lower with caplacizumab than with placebo (12% vs. 49%, P<0.001). The percentage of patients who had a recurrence of TTP at any time during the trial was 67% lower with caplacizumab than with placebo (12% vs. 38%, P<0.001). Refractory disease developed in no patients in the caplacizumab group and in three patients in the placebo group. Patients who received caplacizumab needed less plasma exchange and had a shorter hospitalization than those who received placebo. The most common adverse event was mucocutaneous bleeding, which was reported in 65% of the patients in the caplacizumab group and in 48% in the placebo group. During the trial treatment period, three patients in the placebo group died. One patient in the caplacizumab group died from cerebral ischemia after the end of the treatment period. CONCLUSIONS: Among patients with TTP, treatment with caplacizumab was associated with faster normalization of the platelet count; a lower incidence of a composite of TTP-related death, recurrence of TTP, or a thromboembolic event during the treatment period; and a lower rate of recurrence of TTP during the trial than placebo. (Funded by Ablynx; HERCULES ClinicalTrials.gov number, NCT02553317 .).
EVALuna2:52971